2005
DOI: 10.1128/jcm.43.9.4616-4622.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced PCR Sensitivity Due to Impaired DNA Recovery with the MagNA Pure LC Total Nucleic Acid Isolation Kit

Abstract: The increasing demand for molecular diagnostics in clinical microbiology laboratories necessitates automated sample processing. In the present study, we evaluated the performance of the MagNA Pure LC total nucleic acid isolation kit (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Comparable sensitivities for all of the methodologies were obtained with all specimen types except urine, in which case QiaAmp extraction was two times less sensitive. On the other hand, Schuurman et al (15) mentioned that MagNa Pure extraction of spiked CMV in whole blood showed a 5-to 10-fold reduction in PCR sensitivity compared to the manual nucleic acid extraction according to VOL. 45, 2007 NUCLEIC ACID EXTRACTION WITH easyMAG 423 Boom et al (3).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable sensitivities for all of the methodologies were obtained with all specimen types except urine, in which case QiaAmp extraction was two times less sensitive. On the other hand, Schuurman et al (15) mentioned that MagNa Pure extraction of spiked CMV in whole blood showed a 5-to 10-fold reduction in PCR sensitivity compared to the manual nucleic acid extraction according to VOL. 45, 2007 NUCLEIC ACID EXTRACTION WITH easyMAG 423 Boom et al (3).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, molecular diagnostics have become routine in clinical laboratories (31,32); thus, this study assessed the performance of DNA extraction methods for use in real-time PCR diagnostic assays for Brucella spp. It is widely accepted that DNA extraction methods can influence the sensitivity of molecular diagnostic tests at the levels of DNA yield, purity, and damage (28).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of molecular diagnostics has resulted in increased numbers of specimens submitted to clinical laboratories and has necessitated automation of the processing procedures (32). Given that DNA extraction methods can influence the sensitivity of real-time PCR assays (6), selection of an optimal extraction method is critical for the laboratory detection of Brucella spp.…”
mentioning
confidence: 99%
“…Repeat testing for automated DNA extraction using venous blood was not possible due to insufficient sample at the time of testing and it was not possible to trace the infant for repeat blood draw. Persistence of false negative results following processing of DBS and venous blood samples by the MP has been previously reported by other studies (Patton et al, 2007;Schuurman et al, 2005). The study showed that the specificity of the assay with all DNA extraction methods was 99.6% (95% CI; 97.9 to 100%).…”
Section: Discussionmentioning
confidence: 53%